Syngas Production from Methane Dry Reforming over Ni/SBA-15 Catalyst: Effect of Operating Parameters - Omoregbe, Osaze; Tan, Ji Siang; Danh, Huong T.; Setiabudi, H. D.; Abidin, S. Z.; Vo, Dai-Viet N. (ACS meeting, 2016)
The influence of operating conditions including reactant partial pressure and reaction temperature on the catalytic performance of Ni/SBA-15 catalyst for methane dry reforming (MDR) has been investigated in this study. MDR reaction was carried out under 1 atm with varying CO2/CH4 ratios from 1/2.5 to 2.5/1 at gas hourly space velocity (GHSV) of 24 L gcat-1 h-1 and 923-1023 K. The catalyst was characterized using XRD, FESEM, H2-TPR, BET surface area and TPO measurements. FESEM results showed that Ni particles were well dispersed on nanorod-shaped SiO2 support. Both CH4 and CO2 conversions increased with rising reaction temperature and reached to about 88.2% and 92.9%, respectively at 1023 K and CO2/CH4=1:1. Catalytic activity appeared to be stable with time-on-stream at 973-1023 K whilst a slight drop in activity was observed at 923 K reasonably due to deposited carbon formed by thermodynamically favoured Boudouard and CH4 decomposition reactions. The increase in H2/CO ratio from 1.2-1.4 with growing reaction temperature was ascribed to the enhancement of H2 production through CH4 dehydrogenation. Interestingly, the ratio of CH4 to CO2 conversions increased linearly with CO2 partial pressure whilst an opposite trend was observed for H2/CO ratio suggesting the rising CO2 consumption through concomitant CO2 gasification reaction at CO2-rich environment.